PEMBELAJARAN MENULIS TEKS PERSUASI MENGGUNAKAN METODE CONTEXTUAL TEACHING AND LEARNING - Oky Muhamad Ridwan; Wikanengsih Wikanengsih; Diena San Fauziya (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
This research was conducted to examine learning to write persuasion texts which generally still raises various problems, namely the difficulty of students in starting to write, difficulties in expressing ideas, and difficulty of students in finding writing ideas that are invitations and persuasions to be put into writing. This research was conducted on students of class VIII MTS Darul Ma'arif with research subjects totaling 20 students. The formulation of the problems faced in this study is how difficult are students in learning to write persuasion texts? This study aims to answer the problem formulation regarding students' difficulties in writing persuasion texts and to find out an increase in the results of the initial and final test scores in learning persuasion writing. This research method uses descriptive qualitative which aims to describe the learning outcomes of writing persuasion texts using the contexrual teaching and learning method. The data collection technique in this study was a writing skill test. Based on the results of writing tests carried out in learning activities, the students' initial test got an average score of 50, and the final test got an average score of 78. These results prove that there is a difference between the mean score of the initial test and the final test, which is a difference of 28. With Thus, learning to write persuasion texts using the contextual teaching and learning method can be declared effective and able to become a new innovation in learning activities to write persuasion texts.